A 2-year calorie restriction intervention reduces glycomic biological age biomarkers - Pribić, Tea; Das, Jayanta K; Đerek, Lovorka; Belsky, Daniel W; Orenduff, Melissa; Huffman, Kim M; Kraus, William E; Deriš, Helena; Šimunović, Jelena; Štambuk, Tamara; Hodžić, Azra Frkatović; Kraus, Virginia B; et al. (medRxiv : the preprint server for health sciences, 2024)
In a subset of participants from the CALERIE Phase 2 study we evaluated the effects of 2y of ~25% Calorie Restriction (CR) diet on IgG N-glycosylation (GlycAge), plasma and complement C3 N-glycome as markers of aging and inflammaging. Plasma samples from 26 participants in the CR group who completed the CALERIE2 trial and were deemed adherent to the intervention (~>10 % CR at 12 mo) were obtained from the NIA AgingResearchBiobank. Glycomic investigations using UPLC or LC-MS analyses were conducted on samples from baseline (BL), mid-intervention (12 mo) and post-intervention (24 mo), and changes resulting from the 2y CR intervention were examined. In addition, anthropometric, clinical, metabolic, DNA methylation (epigenetic) and skeletal muscle transcriptomic data were analyzed to identify aging-related changes that occurred in tandem with the N-glycome changes. Following the 2y CR intervention, IgG galactosylation was higher at 24mo compared to BL (p = 0.051), digalactosylation and GlycAge (the IgG-based surrogate for biological age) were not different between BL and 12mo or BL and 24mo, but increased between 12mo and 24mo (p = 0.016, 0.027 respectively). GlycAge was also positively associated with TNF-α and ICAM-1 (p=0.030, p=0.017 respectively). Plasma highly branched glycans were decreased by the 2y intervention (BL vs 24 mo: p=0.013), but both plasma and IgG bisecting GlcNAcs were increased (BL vs 24mo: p<0.001, p = 0.01 respectively). Furthermore, total complement C3 protein concentrations were reduced (BL vs 24mo: p <0.001), as were Man9 glycoforms (BL vs 24mo: p<0.001), and Man10 (which is glucosylated) C3 glycoforms (BL vs 24mo: p = 0.046). 24-mos of CR was associated with several favorable, anti-aging, anti-inflammatory changes in the glycome: increased galactosylation, reduced branching glycans, and reduced GlycAge. These promising CR effects were accompanied by an increase in bisecting GlcNAc, a known pro-inflammatory biomarker. These intriguing findings linking CR, clinical, and glycomic changes may be anti-aging and inflammatory, and merit additional investigation.